2019
DOI: 10.1590/2179-10742019v18i31577
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Metamaterial Antenna for Terahertz Applications

Abstract: In this paper, the metamaterial based rectangular microstrip patch antenna is proposed and designed for THz applications. The circular split ring resonator is implemented as metamaterial. By incorporating metamaterial in the conventional microstrip patch antenna, the size is reduced and the performance of antenna is improved. The proposed antenna has the dimensions of 180 × 212 ×10 µm 3 which is designed on Quartz substrate which is fed by microstrip line feed technique. Additionally, the performance of the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(22 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…It is used to manipulate and control the important characteristics of electromagnetic waves (EM). These EM waves are used to analyze different types of functional devices with various advantages including modulators (Zhou, 2011), filters (Asl, 2020), antenna (Devapriya, 2020), the slow light effect (Liu, 2019), cloaking (Chai, 2019), electromagnetically induced transparency (Cheng, 2019) and fano resonance (Xie, 2018). Because of the ultra-thin dielectric layer thickness, the MMAs drew great attention in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…It is used to manipulate and control the important characteristics of electromagnetic waves (EM). These EM waves are used to analyze different types of functional devices with various advantages including modulators (Zhou, 2011), filters (Asl, 2020), antenna (Devapriya, 2020), the slow light effect (Liu, 2019), cloaking (Chai, 2019), electromagnetically induced transparency (Cheng, 2019) and fano resonance (Xie, 2018). Because of the ultra-thin dielectric layer thickness, the MMAs drew great attention in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…In literature, several geometries are characterized as MTMs structures that are applied in the patch, within the substrate and in the ground plane of MPAs, aiming to optimize their performance and its parameters [1], [3]- [15]. For projects with metamaterials in the patch, it was proposed in [1], to use a Capacitive Loaded Split Rectangular Loop (CLL) resonator to reduce and control the propagation of electromagnetic waves.…”
Section: Introductionmentioning
confidence: 99%
“…On the ground plane, an antenna for the frequencies global system for mobile communications (GSM), worldwide interoperability for microwave access (WiMAX), Bluetooth and WLAN [11], obtained a reduction in electromagnetic absorption with MTM SRR in hexagonal rings, by 66.47% and 66.52% for 1.8 GHz and 2.4 GHz. In a THz antenna [15], a circular shaped Split Ring Resonator (SRR) is used to construct the MTM surface. It obtained reduced antenna, S11 of -65 dB and the gain changed significantly in 1.02 THz.…”
Section: Introductionmentioning
confidence: 99%
“…The inference attained from the design was the improvement of 128% in bandwidth. Amalraj Taksala et al 27 demonstrated the metamaterial MPA with reduced dimensions (180 × 212 × 10 μm 3 ) over the quartz substrate where the circular SRR acted as a patch which resonated at 1.02 THz with an RL of −65 dB. Vettikalladi et al 28 examined the THz antenna with a single dipole and reflector.…”
Section: Introductionmentioning
confidence: 99%